Jerusalem Through the Eyes of Armenian Photographers: Garabed Krikorian, Johannes Krikorian, Elia Kahvedjian - Herkelian, Herag (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The article is dedicated to the development of the art of photography in Jerusalem, the foundation of which was laid by Armenians. The three presented photographs reflect the episodes and realities of the daily life of the inhabitants of Jerusalem in the first half of the 20th century – until the beginning of the Second World War. The authors are Garabed Krikorian, Johannes Krikorian and Elia Kahvedjian. The work of Armenian photographers is a special documentary material about Jerusalem at the end of the 19th century – the beginning of the 20th century, becoming an important contribution to the history of Jerusalem. They are the pioneers of photography in the Middle East. The Armenians of Jerusalem connect their history with the history of the Jewish people, since both peoples suffered many trials, including genocide. However, both peoples survived and continue to coexist side by side in the Old City, bringing them together and uniting them. Հոդվածը նվիրված է Երուսաղեմում լուսանկարչության արվեստի զարգացմանը, որի հիմքը հայերն են դրել։ Ներկայացված երեք լուսանկարներն արտացոլում են Երուսաղեմի բնակիչների առօրյա կյանքի դրվագներն ու իրողությունները XX դարի առաջին կեսին` մինչև Երկրորդ համաշխարհային պատերազմի սկիզբը։ Հեղինակներն են Կարապետ Գրիգորյանը, Հովհաննես Գրիգորյանը և Էլիա Քահվեջյանը։ Հայ լուսանկարիչների ստեղծագործությունն առանձնահատուկ վավերագրական նյութ է XIX դարի վերջի - XX դարի սկզբի Երուսաղեմի մասին՝ դառնալով կարևոր ներդրում Երուսաղեմի պատմության մեջ։ Նրանք Մերձավոր Արևելքի լուսանկարչության ռահվիրաներն են։ Երուսաղեմի հայերն իրենց պատմությունը կապում են հրեա ժողովրդի պատմության հետ, քանի որ երկու ժողովուրդներն էլ կրել են բազմաթիվ փորձություններ՝ ընդհուպ ցեղասպանություն։ Սակայն երկու ժողովուրդներն էլ գոյատևեցին և շարունակում են կողք կողքի համագոյակցել իրենց մերձեցնող և միավորող Հին քաղաքում։ Статья посвящена развитию искусства фотографии в Иерусалиме, основа которого была заложена армянами. Представленные в статье три фотографии имеют цель показать эпизоды и реалии повседневной жизни иерусалимских жителей в первой половине XX в., до начала Второй мировой войны. Авторами этих фотографий являются Карапет Григорян, Ованес Григорян и Элия Ках-веджян. Творчество этих фотографов являет собой своеобразный документальный материал об Иерусалиме конца 19 – начала 20 веков, ставший важным вкладом в историю Иерусалима. Армянские фотографы стали пионерами фотографии на Ближнем Востоке. Армяне Иерусалима связывают свою историю с историей еврейского народа, поскольку на долю обоих народов выпало немало тяжких испытаний вплоть до геноцида. Но оба народа выжили и продолжают сосуществовать бок о бок в городе, который их сближает и объединяет.
Keywords: Armenian photographers